2018
DOI: 10.1002/asia.201800553
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Porous Carbon Materials for Electrochemical Energy Storage

Abstract: Climate change and the energy crisis have promoted the rapid development of electrochemical energy-storage devices. Owing to many intriguing physicochemical properties, such as excellent chemical stability, high electronic conductivity, and a large specific surface area, porous carbon materials have always been considering as a promising candidate for electrochemical energy storage. To date, a wide variety of porous carbon materials based upon molecular design, pore control, and compositional tailoring have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 103 publications
(161 reference statements)
0
57
0
Order By: Relevance
“…In contrast, secondary batteries can deliver high energy density, but their power densities are relatively poor . From the viewpoint of future application, developing advanced energy storage system is urgently needed that deliver both higher energy density and power density . Recently, hybrid lithium‐ion capacitors (LICs) have emerged, which combines the merits of the two systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, secondary batteries can deliver high energy density, but their power densities are relatively poor . From the viewpoint of future application, developing advanced energy storage system is urgently needed that deliver both higher energy density and power density . Recently, hybrid lithium‐ion capacitors (LICs) have emerged, which combines the merits of the two systems.…”
Section: Introductionmentioning
confidence: 99%
“…[11] From the viewpoint of future application, developing advanced energy storage system is urgently needed that deliver both higher energy density and power density. [12] Recently, hybrid lithium-ion capacitors (LICs) have emerged, which combines the merits of the two systems. LICs are constructed from a capacitor-type electrode and a lithium ion battery-type electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the carbonization behavior of carboxylate-functionalized PIMs was scrutinized using TGA-MS, cross-polarization-magic angle spinning (CP-MAS) 13 C NMR, EA, Brunauer-Emmett-Teller (BET), Raman, and X-ray diffraction (XRD). For prepared four distinct types of sub-nanosized membranes with different oxygen-to-carbon ratios, the nanofiltration (NF) performance of the resulting membranes was tested.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, powders and films were chosen as templates to produce graphene by the CVD method . The use of templates is an easy way to create porous structures with different morphologies . Previous contributions have demonstrated that few‐layered graphene films can be generated by using 2 D copper, nickel, or silica foils.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The use of templatesi sa ne asy way to create porous structures with different morphologies. [25] Previous contributions have demonstrated that few-layered graphene films can be generated by using 2D copper,n ickel, or silica foils. However,t he graphene yield is quite low and the transfer process is complicated and time-consuming, which restricts practical mass productiono na ni ndustrial scale.…”
Section: Introductionmentioning
confidence: 99%